2002
DOI: 10.1002/cncr.10260
|View full text |Cite
|
Sign up to set email alerts
|

Results with chemotherapy comprised of cyclophosphamide, doxorubicin, vincristine, and prednisone followed by radiotherapy with or without prechemotherapy surgical debulking for patients with bulky, aggressive lymphoma

Abstract: BACKGROUNDThe authors performed a case–control analysis of local control, progression free survival, and overall survival in patients with Stage I–II aggressive lymphomas measuring ≥ 7 cm in greatest dimension who were treated initially with or without surgical debulking: All patients then received cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP)‐based chemotherapy followed by involved‐field radiotherapy.METHODSFrom May 1975 through May 1996, 50 patients were treated with (n = 25 patients) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Overall survival at 7 years was significantly better in patients undergoing debulking surgery (93% versus 35%). This finding was confirmed by Wilder et al 15 lymphoma patients treated with CHOP and radiotherapy. At 5 years, local control rate (96% versus 80%), progression-free survival (88% versus 62%), and overall survival (83% versus 71%) were better after debulking than after chemoradiotherapy alone.…”
Section: Discussionsupporting
confidence: 67%
“…Overall survival at 7 years was significantly better in patients undergoing debulking surgery (93% versus 35%). This finding was confirmed by Wilder et al 15 lymphoma patients treated with CHOP and radiotherapy. At 5 years, local control rate (96% versus 80%), progression-free survival (88% versus 62%), and overall survival (83% versus 71%) were better after debulking than after chemoradiotherapy alone.…”
Section: Discussionsupporting
confidence: 67%
“…However, in scenarios where chances of performing a randomized trial is slim [e.g. for ÿnding the value of prechemotherapy surgical debulking for patients with bulky, aggressive lymphoma [12]; Role of high-dose chemotherapy with peripheral blood stem cell transplantation for patients with primary systemic amyloidosis as opposed to standard chemotherapy [7], etc. ], the evidence from well performed non-randomized trial are adopted for treatment decision making, specially if the outcomes can be conÿrmed on a series of such studies yielding results of similar magnitude and directionality.…”
Section: Discussionmentioning
confidence: 99%
“…For maxillary sinus DLBCL, the main purpose of surgery is for biopsy, but it has the effect of maximally reducing tumor cells before radiation therapy to be performed later, and has the effect of alleviating the symptoms complained by the patient. Therefore, during surgery, it is necessary to reduce the size of the tumor tissue as much as possible to the extent that the surrounding tissues can be preserved and to collect sufficient specimens for biopsy [8]. For the case of this study, all tissues that were able to be observed with endoscopy during the surgery were removed, and after the surgery, the patient's symptoms such as epiphora, facial pain, and eye pain improved immediately, and an accurate diagnosis was possible through biopsy.…”
mentioning
confidence: 99%